2017
DOI: 10.1136/bjsports-2017-097956
|View full text |Cite
|
Sign up to set email alerts
|

Sports injury and illness incidence in the Rio de Janeiro 2016 Olympic Summer Games: A prospective study of 11274 athletes from 207 countries

Abstract: Objective To describe the pattern of injuries and illnesses sustained during the Games of the XXXI Olympiad, hosted by Rio de Janeiro from 5 to 21 August 2016. Methods We recorded the daily incidence of athlete injuries and illnesses (1) through the reporting of all National Olympic Committee (NOC) medical teams and (2) in the polyclinic and medical venues by the Rio 2016 medical staff. results In total, 11 274 athletes (5089 women, 45%; 6185 men, 55%) from 207 NOCs participated in the study. NOC and Rio 2016 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
390
11
10

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 340 publications
(429 citation statements)
references
References 90 publications
18
390
11
10
Order By: Relevance
“…A total of 11 274 athletes (5089 women (45%), 6185 men (55%)) from 207 Olympic teams participated in the IOC’s surveillance study 17. NOC and Rio de Janeiro 2016 medical staff reported 1101 injuries.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 11 274 athletes (5089 women (45%), 6185 men (55%)) from 207 Olympic teams participated in the IOC’s surveillance study 17. NOC and Rio de Janeiro 2016 medical staff reported 1101 injuries.…”
Section: Resultsmentioning
confidence: 99%
“…All National Olympic Committee (NOC) medical teams reported the daily occurrence (or non-occurrence) of injuries on a standardised medical report form 17. We also retrieved the same information on all athletes treated for injuries in the polyclinic and all other medical venues by the Organising Committee of the Rio de Janeiro 2016 medical staff.…”
Section: Methodsmentioning
confidence: 99%
“…Water polo has higher rates of contact injuries than the other aquatic disciplines of swimming, diving, synchro and open-water swimming 13–15. During the 2016 Rio OG, water polo had the highest injury rates of all team sports 19. Water polo has a ‘machismo’ sport culture, and thus risk reduction interventions targeting contact injuries should address a cultural change with the water polo stakeholders.…”
Section: Discussionmentioning
confidence: 99%
“…The present study analysed all water polo injuries reported during four Summer OG (2004,16 2008,17 2012,18 201619 and four FINA WCh (2009,13 2013,14 2015,15 2017). The study design, study implementation, injury definition, data collection and analysis procedures were similar at all tournaments, and have previously been described in detail 13–19…”
Section: Methodsmentioning
confidence: 99%
“…Injuries are common in professional football, not only in comparison with other professions but also in comparison with other sports. During the summer Olympics in Beijing 2008, London 2012 and Rio de Janeiro 2016, football was among the sports with the highest injury rate [21][22][23]. An injury that results in a player being unable to take a full part in future football training or match play *Definitions according to a consensus statement about epidemiological research in football [24].…”
Section: The Injury Problem In Professional Footballmentioning
confidence: 99%